Analysis of wind speed and direction as support for green buildings in urban areas using the weibull method - Yudi Kurniawan; Ida Bagus Dharmawan; Wahyu Anhar; Akhmad Nurdin (Politeknik Negeri Lhokseumawe, 2023)
Currently, the dominance of electricity in Indonesian providers comes from fossil energy which has the potential to increase the average temperature in various parts of the world or is called global warming. The contribution of the national renewable energy potential mix in 2016 ranging from 6.27%, then reaching 11.28% in 2020. The Government has made a long-term plan for the national renewable energy mix to reach 25% in 2025 and 31% in 2050. One of the renewable energy sources is wind energy, which is usually built on a large scale and is separated from settlements so that a long distribution network is required. Conversely, on a small scale, wind energy can be utilized with a simpler distribution network, this concept is called Small Wind Turbine. For a good wind turbine is designed according to the wind characteristics in real-time, so it is necessary to study wind mapping. This research was conducted as a prelude to observing wind characteristics in the form of mapping wind speed and direction in real-time in the northern part of Balikpapan City Region, using the Automatic Weather Station instrument which was carried out August 6 to September 26, 2022. Data processing in this study using the Weibull distribution method with Microsoft Excel. This study shows an average speed of 1.118 m/s in wind conditions with high wind variability with strong gusts, with a power density value of 1.157 Watts/m2. The wind direction tends to be east after the wind gusts are blocked by the building profile.